One God, one Lord early Christian devotion and ancient Jewish monotheism - Hurtado, Larry W., 1943- (London, UK T. and T. Clark, 1998)
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Jewish Christians -- History -- Early church, ca. 30-600.; God (Judaism) -- History of doctrines; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity